Cannabis, Tobacco, Alcohol Use, and the Risk of Early Stroke: A Population-Based Cohort Study of 45 000 Swedish Men. Issue 2 (February 2017) - Falkstedt, Daniel; Wolff, Valerie; Allebeck, Peter; Hemmingsson, Tomas; Danielsson, Anna-Karin
Abstract : Background and Purpose—: Current knowledge on cannabis use in relation to stroke is based almost exclusively on clinical reports. By using a population-based cohort, we aimed to find out whether there was an association between cannabis use and early-onset stroke, when accounting for the use of tobacco and alcohol. Methods—: The cohort comprises 49 321 Swedish men, born between 1949 and 1951, who were conscripted into compulsory military service between the ages of 18 and 20. All men answered 2 detailed questionnaires at conscription and were subject to examinations of physical aptitude, psychological functioning, and medical status. Information on stroke events up to ≈60 years of age was obtained from national databases; this includes strokes experienced before 45 years of age. Results—: No associations between cannabis use in young adulthood and strokes experienced ⩽45 years of age or beyond were found in multivariable models: cannabis use >50 times, hazard ratios=0.93 (95% confidence interval [CI], 0.34–2.57) and 0.95 (95% CI, 0.59–1.53). Although an almost doubled risk of ischemic stroke was observed in those with cannabis use >50 times, this risk was attenuated when adjusted for tobacco usage: hazards ratio=1.47 (95% CI, 0.83–2.56). Smoking ≥20 cigarettes per day was clearly associated both with strokes before 45 years of age, hazards ratio=5.04 (95% CI, 2.80–9.06), and with strokes throughout the follow-up, hazards ratio=2.15 (95% CI, 1.61–2.88). Conclusions—: We found no evident association between cannabis use in young adulthood and stroke, including strokes before 45 years of age. Tobacco smoking, however, showed a clear, dose–response shaped association with stroke.